Do People Anticipate Loss Aversion? - Imas, Alex; Sadoff, Sally; Samek, Anya (Management Science, 2017)
There is growing interest in the use of loss contracts that offer performance incentives as up-front payments that employees can lose. Standard behavioral models predict a trade-off in the use of loss contracts: employees will work harder under loss contracts than under gain contracts, but, anticipating loss aversion, they will prefer gain contracts to loss contracts. In a series of experiments, we test these predictions by measuring performance and preferences for payoff-equivalent gain and loss contracts. We find that people indeed work harder under loss than gain contracts, as the theory predicts. Surprisingly, rather than a preference for the gain contract, we find that people actually prefer loss contracts. In exploring mechanisms for our results, we find suggestive evidence that people do anticipate loss aversion but select into loss contracts as a commitment device to improve performance, using one bias, loss aversion, to address another, dynamic inconsistency. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2402 . This paper was accepted by Teck-Hua Ho, behavioral economics.